Postbuckling Analysis of Shear Deformable FGM Cylindrical Shells with Porosities Subjected to Combined Mechanical Loads in Thermal Environments (Advances in Applied Mathematics and Mechanics, 2025)
Motivated by evident lack of studies on the nonlinear stability of porousfunctionally graded cylindrical shells under combined mechanical loads, this paperpresents an effective analytical approach to investigate the postbuckling behavior ofmoderately thick functionally graded circular cylindrical shells with porosities subjected to combined action of axial compression and external pressure in thermal environments. Porosities are evenly or unevenly distributed within the functionally gradedmaterial (FGM). Due to presence of porosities, effective properties of the FGM are determined using a modified version of linear rule of mixture. Formulations are basedon first order shear deformation theory taking into account von Kármán-Donnell non-linearity. Analytical solutions of deflection and stress function are assumed to satisfy simply supported boundary conditions and Galerkin method is adopted to deriveclosed-form results of buckling loads and nonlinear load-deflection relations. Parametric studies are carried out to evaluate the effects of material and geometry properties, preexisting mechanical loads and temperature, distribution type and volumefraction of porosity on the postbuckling load carrying capacity of porous FGM cylindrical shells.